Konsep Masyarakat Madani dalam Perspektif Islam dan Demokrasi serta Relevansinya bagi Kehidupan Sosial di Indonesia - MUFARRIHAH, NAISYILA FAIZATUL (Maliki Interdisciplinary Journal, 2026)
The concept of civil society refers to a civilized social order that upholds democratic values, justice, equality, freedom, and respect for human rights. From an Islamic perspective, the concept of civil society has strong theological and historical foundations, particularly reflected in the life of the Madinan community during the time of Prophet Muhammad SAW. The Madinan society was built upon the principles of monotheism, justice, brotherhood, tolerance, and deliberation. This article aims to examine the concept of civil society from an Islamic perspective and analyze its relevance to social life in Indonesia, a plural and multicultural country. The research method used is library research by examining primary sources such as the Qur’an and Hadith, as well as secondary sources including books and scientific journals. The results indicate that the values of civil society in Islam are highly relevant to Indonesia’s national values, such as social justice, unity, religious tolerance, and public participation in social and political life. Therefore, strengthening the concept of civil society based on Islamic values can contribute to building a harmonious, just, and civilized social life in Indonesia.